The oxford handbook of human motivation - Ryan, Richard M. (New York : Oxford University Press, 2012)
The Oxford Handbook of Human Motivation collects together the field's top theorists and researchers to provide overviews of today's most noteworthy theories, topical chapters on phenomena from ego-depletion to flow, recent work on the biological bases of motivation, and applied in chapters on therapy, work, sport, education and relationships.
Part One: Introduction -- Part Two: General Theories of Human Motivation -- Part Three: Motivational Processes -- Part Four: Goals and Motivation -- Part Five: Motivation in Relationships -- Part Six: Evolutionary and Biological Perspectives -- Part Seven: Motivation in Application
Includes index.
Keywords: MOTIVATION (PSYCHOLOGIC)